2005
DOI: 10.1152/ajprenal.00451.2004
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular abundance of nephrin and podocin in experimental nephrotic syndrome: different effects of antiproteinuric therapies

Abstract: are not yet fully clarified, it is well accepted that nephrin and podocin are involved in the development of proteinuria. The effects of early treatment with various antiproteinuric therapies on proteinuria and glomerular staining of nephrin and podocin in rats with experimental NS have not been previously studied. Proteinuria and glomerular nephrin and podocin immunofluorescence were examined in rat kidneys with adriamycin-induced NS and the effects of antiproteinuric drug therapies during 5 wk with enalapril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 54 publications
5
15
0
Order By: Relevance
“…33,34 Thus, one possible explanation for our discrepant results may be due to our use of ACEi at maximal dose. Although ARB has been shown to suppress renal injury in experimental CKD, 11,35 our results are in agreement with the previous observation by Nakhoul et al 36 that enalapril but not losartan reduced proteinuria in ADR rats, and that ACEi/ ARB combination did not provide advantageous antiproteinuric responses. 24,36 Similarly, Yilmaz et al 37 also reported a lack of anti-proteinuric effect with losartan in ADR rats.…”
Section: Discussionsupporting
confidence: 92%
“…33,34 Thus, one possible explanation for our discrepant results may be due to our use of ACEi at maximal dose. Although ARB has been shown to suppress renal injury in experimental CKD, 11,35 our results are in agreement with the previous observation by Nakhoul et al 36 that enalapril but not losartan reduced proteinuria in ADR rats, and that ACEi/ ARB combination did not provide advantageous antiproteinuric responses. 24,36 Similarly, Yilmaz et al 37 also reported a lack of anti-proteinuric effect with losartan in ADR rats.…”
Section: Discussionsupporting
confidence: 92%
“…Adriamycin (ADR) nephrosis is well known as a nephrosis and FSGS model in rats [14,15]. An LPS-induced nephrosis model has been established in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Homeostatic mechanisms are unable to cope with such urinary protein losses, and the resulting hypoalbuminemia frequently leads to edema. 1,2 The glomerular damage that is characteristic of NS can also result in urinary loss of lipids and other plasma proteins, including some of the apolipoproteins. 3 Another important feature of the NS is hyperlipidemia characterized by increased plasma concentrations of very-low-density (VLDL), intermediatedensity, low-density lipoproteins (LDL) and, as the disorder progresses, also by hypertriglyceridemia and decreased concentrations of high-density lipoproteins (HDL).…”
Section: Introductionmentioning
confidence: 99%